الاستثمار والتسويق في حقوق النقل التلفزيوني والدعاية والاعلام الرياضي من وجهة نظر الهيئات الادارية لأندية بغداد (Journal of the College of Basic Education, 2022)
The research included five chapters. The first chapter contained the introduction of the research, its importance, and the objectives of the research. Building a measure for investment and sports marketing in the rights of television broadcasting, advertising and sports media for the administrative bodies of Baghdad sports clubs. And to identify the reality of investment and marketing in the rights of television transmission, publicity and sports media for Baghdad sports clubs. The researcher used the descriptive approach. In the survey method, the research community was represented by (432) president, deputy and members. The researcher built a measure of investment and sports marketing in the rights of television broadcasting, advertising and sports media for Baghdad sports clubs for the work of the clubs. He prepared a special questionnaire and phrases for data collection and adoption.